News consumption through SNS platforms:Extended motivational model - Ahmed, Ismail Sheikh Yusuf; Idid, Syed Arabi; Ahmad, Zeti Azreen (Media Watch, 2018)
The emergence of new media technologies has redefined how people, particularly the youth, are exposed to the news. Social networking sites (SNS), in particular, have widely changed the manner in which news is consumed. SNS platforms have emerged as news sources where people engage in several activities such as sharing, commenting and discussing news with peers, acquaintances and family members. Thus, drawing on the extended version of the motivational model, this study attempts to determine contributing factors. Using a stratified random sampling procedure, this study compiles a sample from leading higher education institutions in a Sub-Saharan African country. The data are then analysed using a structural equation modelling technique with SmartPLS software and the both the validity and reliability indexes are reported. The findings suggest that students' attitude towards news consumption (ATT) via SNS platforms is influenced directly by perceived usefulness (PU), perceived enjoyment (PE) and subjective norms (SN) and indirectly by PE and SN factors. In addition, PU and PE are positively predicted by SN. Furthermore, ATT directly predicts SNS news consumption (SNC), while PU, PE and SN indirectly contribute to SNC.